MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA MENGGUNAKAN PENDEKATKAN PEMBELAJARAN SAINTIFIK DI MTS RABITATUS SA’ADAH TAHUN PELAJARAN 2019/2020 - kartini, april lia; Masjudin, Masjudin (Media Pendidikan Matematika, 2020)
Abstract: The learning process of teachers tends to use conventional models during the learning process takes place, students are only focused on listening to the delivery of lessons given by the teacher, whereas between one student and other students there is no visible communication relationship, because when learning activities take place students only listen to the teacher’s explanation and note material presented by the teacher. This results in the low student learning outcomes. The purpose of this study is to improve the process and student learning outcomes of mathematics through a scientific approach to the circle material in class VIII students of MTs Rabitatus Saâ€™adah. This type of research used in this research is classroom action research which consists of two cycles, each cycle consisting of 4 stages including, 1) planning, 2) implementation, 3) observation, 4) reflection. This research instrument uses student and teacher observation sheets and question sheets. The results showed that in cycle 1 the classical completeness of students reached 65%. Then in the second cycle the classical completeness of students reaches 85%. Based on the results of data analysis and discussion, it can be concluded that through scientific learning can improve the activities and learning outcomes of students of class VIII MTs Rabitatus Saadah 2018/2019 academic year.